2018
DOI: 10.1007/s10735-018-9763-6
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 and epithelial–mesenchymal transition proteins in colorectal carcinoma: an immunohistochemical study

Abstract: Epithelial-mesenchymal transition (EMT) plays an important role in cancer metastasis. During EMT, tumor cells acquire the capacity to migrate and invade the stroma. Activation of the transforming growth factor-b (TGF-b) signaling pathway is of major importance for the initiation of EMT. Smad4, an essential protein of this pathway, is known to complex with multiple transcription factors (e.g. Snail-1, Slug, Twist-1), in various types of cancer, promoting the repression or activation of target genes. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
3
20
1
1
Order By: Relevance
“…Smad4 plays an important role in TGF-β-induced EMT. Studies have shown that Smad4 as a central component of EMT transition in human CRC to down-regulate E-cadherin expression 39. Similar to these findings our data indicated that curcumin significantly inhibited Smad4 entry into the nucleus.…”
Section: Discussionsupporting
confidence: 89%
“…Smad4 plays an important role in TGF-β-induced EMT. Studies have shown that Smad4 as a central component of EMT transition in human CRC to down-regulate E-cadherin expression 39. Similar to these findings our data indicated that curcumin significantly inhibited Smad4 entry into the nucleus.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, TGF-β/smad signalling downregulates the expression of ZO-1, Claudin-1, and cytokeratins, followed by the degradation of tight junctions and the upregulation of N-cad expression 43,44 . In the classical pathway, SMAD4, as the common partner smad (co-SMAD), forms complexes with p-SMAD2/p-SMAD3 and then translocates into the nucleus and regulates the transcription of target genes through interactions with other DNA-binding TFs, such as snail/slug 45 . We found that SMAD4 expression significantly increased with NDRG1 overexpression but decreased with NDRG1 knockdown, primarily causing the alteration of Cytokeratin 7, Claudin-1 and N-cad expression, suggesting that NDRG1 might influence the process of EMT through modulating the expression of SMAD4 and slug in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT7 overexpression inhibits EMT in OSCC, where SIRT7 expression correlates inversely with patient survival. Overexpression of SIRT7 strongly decreased OSCC migration and invasion, increased E-cadherin and downregulated VIMENTIN and MMP7 protein levels by deacetylating SMAD4, a key regulator of EMT (Levy and Hill, 2005; Ioannou et al, 2018; Li et al, 2018). In contrast with other studies (Barber et al, 2012; Yu et al, 2014; Malik et al, 2015), this report provides evidence of a new role for SIRT7 in tumor metastasis.…”
Section: Role Of Sirtuins In Emtmentioning
confidence: 99%